2023
DOI: 10.3390/toxics11010048
|View full text |Cite
|
Sign up to set email alerts
|

Diosmin Mitigates Gentamicin-Induced Nephrotoxicity in Rats: Insights on miR-21 and -155 Expression, Nrf2/HO-1 and p38-MAPK/NF-κB Pathways

Abstract: Gentamicin (GNT) is the most frequently used aminoglycoside. However, its therapeutic efficacy is limited due to nephrotoxicity. Thus, the potential anticipatory effect of Diosmin (DIOS) against GNT-prompted kidney damage in rats together with the putative nephroprotective pathways were scrutinized. Four groups of rats were used: (1) control; (2) GNT only; (3) GNT plus DIOS; and (4) DIOS only. Nephrotoxicity was elucidated, and the microRNA-21 (miR-21) and microRNA-155 (miR-155) expression and Nrf2/HO-1 and p3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…6 In agreement with previous studies, the current investigation demonstrated that GEN insult resulted in a significant decrease of Nrf2, associated with a significant increase of NF-κB p65 in rat kidneys. 8,9 The current study also revealed that PNG treatment significantly restored the balance between the two pathways, as indexed by the significant increment of Nrf2, and the significant decrement of NF-κB p65 in kidneys of GEN-challenged rats. Similarly, prior investigations showed that PNG protected against oxidative stress, inflammation, and apoptosis through upregulation of Nrf2 pathway and inhibition of NF-κB pathway.…”
Section: Histopathological Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…6 In agreement with previous studies, the current investigation demonstrated that GEN insult resulted in a significant decrease of Nrf2, associated with a significant increase of NF-κB p65 in rat kidneys. 8,9 The current study also revealed that PNG treatment significantly restored the balance between the two pathways, as indexed by the significant increment of Nrf2, and the significant decrement of NF-κB p65 in kidneys of GEN-challenged rats. Similarly, prior investigations showed that PNG protected against oxidative stress, inflammation, and apoptosis through upregulation of Nrf2 pathway and inhibition of NF-κB pathway.…”
Section: Histopathological Resultssupporting
confidence: 69%
“…6,7 Previous investigations showed that GEN-induced renal toxicity caused by a marked disruption in the balance between Nrf2 and NF-κB pathways resulting in augmented oxidative stress, inflammatory responses, and cell apoptosis. 8,9 Punicalagin (PNG) is a biologically active polyphenolic ingredient obtained from pomegranate (Punica granatum). It was reported that PNG had antioxidant, anti-inflammatory, and antiapoptotic properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, diosmin (100 mg/kg) prompted minimal inflammatory cell infiltration into the renal tubule cortex. The anti-inflammatory compound diosmin reduced the count of TNF-α, IL-1β, p38 mitogen-activated protein kinase (p38MAPK), and nuclear factor kappa B (NF-ĸB) cells ( Nadeem et al, 2023 ). Consistent with the current findings, Haghighi et al (2012) reported a decrease in animal body weight following nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Chrysin [175] miR-92a-3p [176], let-7a-5p, miR-9-5p, miR-22-3p [177], miR-34a-5p [177,178], miR-126-3p [177] Chlorogenic acid [179] miR-199a-5p [180] miR-18a-5p [177], miR-21-5p [181,182], miR-221-3p [177] ↓ Daidzein [5] miR-122-5p [183] Diosmin [184] miR-21-5p [181,182] Delphinidin [185] miR-23a-3p [186], miR-204-3p [187] miR-155-5p [181], miR-17-5p [188] ↓ Epigallocatechin gallate (EGCG) [189] miR-30a-5p [190] Melatonin [191] miR-155-5p [192], miR-23a-3p [193] ↓…”
Section: Natural-product-regulated Mirnasmentioning
confidence: 99%